Nomenclatural and distributional notes on Neotropical Cerambycidae (Coleoptera) - Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2018)
The following synonymies are proposed: Chydarteres formosus Galileo & Martins, 2010 as a junior synonym of Andraegoidus fabricii (Dupont, 1838); Nyssosternus Gilmour, 1963 as a junior synonym of Stenolis Bates, 1864; Periestola Breuning, 1943 as a junior synonym of Cobelura Erichson, 1847; Cobelura inornata Monné & Monné, 2017 as a junior synonym of Cobelura strandi (Breuning, 1943), new combination; Cobelura curiosa (Monné & Martins, 1976), new combination, removed from synonymy of Cobelura strandi. Trachyderes (T.) latecinctus Martins, 1975, new status. New state records: Parasphallenum fulguratum (Chabrillac, 1857), newly recorded from Brazil, Amazonas; Melathemma polita Bates, 1870, newly recorded from Brazil, Acre; Trachyderes (T.) latecinctus Martins, 1975, newly recorded from Brazil, Roraima. New country records: Paracleodoxus cineraceus Monné & Monné, 2010, newly recorded from Colombia; Oreodera tuberculata Thomson, 1865, newly recorded from Brazil, Pará; Rhaphiptera avicenniae Dalens & Tavakilian, 2007, newly recorded from Brazil, Pará; Rhaphipteroides apicalis Tavakilian, Dalens & Touroult, 2007, newly recorded from Brazil, Amazonas. The correct type locality of Oncideres ochreostillata Dillon & Dillon, 1952 is given.